Enhancing Arabic Speaking Skills: Pedagogical Strategies and Practical Approaches with special reference to Role-playing - ZUBAIR, Dr K M A AHAMED (RADINKA JAYA UTAMA PUBLISHER, 2025)
This research investigates the development and teaching of speaking skills in Arabic language education, emphasizing effective instructional methods and the importance of continuous practice beyond the classroom. It highlights that achieving proficiency in speaking requires dedicated effort from both teachers and students, utilizing tailored strategies to meet learners' needs. Drawing from extensive literature and pedagogical theories, the study underscores active participation, regular practice, and proper evaluation as key components for improving oral communication. At the New College, Chennai, under the University of Madras, Arabic teaching aims to enhance students’ understanding of texts and their overall language skills—listening, speaking, reading, and writing. However, traditional teaching methods, primarily lecture-based, limit student engagement and reduce motivation to communicate. To address this issue, the study explores the implementation of role-playing strategies, which are highly effective for developing speaking skills by fostering active participation and confidence. The research involved third-year Arabic students and followed two cycles, each with planning, implementation, observation, and reflection phases. Findings reveal that role-playing activities significantly boost students’ speaking abilities, helping them feel less embarrassed and more fluent. Students also work collaboratively, gaining confidence through acting and active engagement in class. Overall, the study demonstrates that incorporating interactive methods like role-playing can substantially improve Arabic speaking skills, encouraging more dynamic and motivated language learning environments. The results suggest that adopting such strategies can lead to more effective language instruction and greater student success in oral proficiency.